Perancangan Aplikasi Bank Sampah Berbasis Website Untuk Kampus Bebas Sampah - Marzuki Marzuki; MS Hasibuan; Dika Tondo W; Ruki Rizal; Winda Rika Lestari (Puslitbang Akademi Relawan TIK Indonesia, 2024)
Waste management on campus has become increasingly crucial in addressing global challenges related to the waste crisis. This research outlines the implementation of a web-based Waste Bank Application at IIB Darmajaya Campus as a strategic step towards achieving the vision of a Zero-Waste Campus. The application is designed to enhance the campus community's participation in waste management through the use of information technology approaches. The research methodology involves application development and impact analysis. The research results indicate that the Waste Bank Application successfully increased awareness and participation of the campus community in waste sorting and recycling. The implementation of a reward point system in the application also proved effective in providing incentives for members, motivating them to contribute more actively. Through effectiveness evaluation, this study concludes that the web-based Waste Bank Application can be a key instrument in realizing a Zero-Waste Campus. These findings make a significant contribution to the literature on community-based waste management and offer practical insights for other educational institutions looking to adopt a similar approach. Policy recommendations and further development strategies are also proposed to support the sustainability of the Zero-Waste Campus program in the future.